Resilience and Persistence of Sustainable Travel and Tourism Industry during the Impact of COVID-19 Pandemic - Warnakulasooriya, W.M.S (NSBM Green University, 2020)
The main objective of this study is to discover the impact of the coronavirus (COVID-19) pandemic on Travel and Tourism industry. This industry is one of the major sources of employment, government revenue, and foreign exchange earnings directly or indirectly for developing and developed countries. Sri Lanka is one of the top travel destinations in the world due to unparalleled natural resources, wildlife, unique cultural heritage, and warm and friendly locals. This industry has become the third-largest export earner of Sri Lanka while supporting the economy in 2019. According to the World Travel and Tourism Council in 2019, Travel and Tourism’s direct, indirect and induced impact accounted for 10.3% of global GDP, 330 million jobs, 1 in 10 jobs around the world. Over the past five years, the sector has created 1 in 4 new jobs. COVID-19 pandemic has triggered an unprecedented crisis in this industry. It resulted 43% (142.6 Million) job lost, 43% ($3,815 Billion USD) GDP loss in globally and 48% (87.4 Million) job lost, 50% ($1,475 Billion USD) GDP loss in Asia Pacific region. Pandemic impacted the global arrival assumption by 65% international and 33% domestic globally and 71% international and 31% domestic in the Asia Pacific region. The data was collected through secondary sources and qualitative analysis was employed. Through this study, strategies were identified, including the challenges, recovery measures, and how-to resilience in the current pandemic situation to overcome the issues identified via the study for sustainable Travel and Tourism industry in Sri Lanka
Keywords: sustainable; travel and tourism; covid-19 impact; resilience; persistence.